Examining Genital Infections in Type 2 Diabetes: A Retrospective Analysis of Three Tertiary Hospitals in South Africa - Thembane, Nokukhanya; Nxumalo, Sihle Bonga; Jaya , Ziningi Nobuhle (Student's Journal of Health Research Africa, 2025)
Abstract Introduction: This study investigated the prevalence and characteristics of genital infections among patients with Type 2 Diabetes (T2D) in KwaZulu-Natal (KZN), South Africa. The increasing prevalence of T2D in the region necessitates understanding its health implications, especially the link between diabetes and genital infections. The study aimed to identify common pathogens and assess the correlation between glycaemic control (HbA1c levels) and infection rates. Method: A retrospective analysis was conducted on laboratory data from 300 T2D patients. The study examined infection rates and identified pathogens, with a focus on the relationship between infection prevalence and HbA1c levels. Results: Of the 300 patients, 73 (24.3%) tested positive for genital infections. Candida species were the most common pathogens, found in 49% of cases. A significant association was found between elevated HbA1c levels and increased infection rates, with patients having HbA1c levels above 7.5% showing the highest frequency of infections. Conclusion: The study highlights the increased risk of genital infections in T2D patients, particularly those with poor glycaemic control. Uncontrolled diabetes, as indicated by elevated HbA1c levels, significantly raises susceptibility to infections. Recommendations: Healthcare providers should increase awareness of genital infection risks in diabetic patients and prioritize regular screenings. Effective glycaemic control, patient education on hygiene, and early medical intervention for infections are essential to improve outcomes and reduce infection rates in T2D patients.